Development of Off-pump Mitral Valve Replacement in a Porcine Model - Gillespie, Matthew J. (Ann Thorac Surg, 2015)
PURPOSE: We describe our initial experience with on-bypass and off-bypass (off-pump) mitral valve replacement with the modified version of our novel catheter-based sutureless mitral valve (SMV2) technology, which was developed to atraumatically anchor and seal in the mitral position. DESCRIPTION: The SMV is a self-expanding device consisting of a custom designed nitinol framework and a pericardial leaflet valve mechanism. For the current studies our original device was modified (SMV2) to reduce the delivery profile and to allow for controlled deployment whilst still maintaining the key principles necessary for atraumatic anchoring and sealing in the MV position. EVALUATION: Ten Yorkshire pigs underwent successful SMV2 device implantation via a left atriotomy (on-pump N=6; off-pump N=4). Echocardiography and angiography revealed excellent LV systolic function, no significant perivalvular leak, no MV stenosis, no left ventricular (LV) outflow tract obstruction and no aortic valve insufficiency. Necropsy demonstrated that the SMV2 devices were anchored securely. CONCLUSIONS: This study demonstrates the feasibility and short-term success of off-pump mitral valve replacement using a novel, catheter-based device in a porcine model.